Pharmacy students' learnings and reflections to inform the development of the 'Working Respectfully with Aboriginal Peoples' (WRAP) Toolkit. Issue 1 (2nd January 2021) - Lucas, Cherie; Aly, Mariyam; Power, Tamara
ABSTRACT: Delivering effective healthcare requires healthcare professionals to reflect on their own cultural background and their patient's cultural needs. Culture is a determinant of health and if not considered, negative health outcomes can result. This is of particular importance when working with Aboriginal communities and caring for Aboriginal people whose views have been excluded from healthcare models, funding, and policy. Non-indigenous healthcare professionals, such as pharmacy students, benefit from understanding Aboriginal peoples' healthcare needs and models of holistic healthcare, as well as reflecting on their own cultures, assumptions, and experiences on placement. This article explores students' views to inform the development of a Toolkit to support students' learning prior to engaging in placements in Aboriginal communities. The study involved collaboration with students, Aboriginal community members, educators experienced in Indigenous health and allied health education. This paper is within a series exploring the development and evaluation of the 'Working Respectfully with Aboriginal People (WRAP): Student Toolkit'.